The Use Of Educational Tools To Develop The Speaking Skills Of Ninth-Graders At Nurul Yaqin Junior High School, Jember - Bambang Irawan; Agil Fahmi Attaufiqi (Journal of Arabic Language Teaching, 2021)
To achieve learning goals, several elements are needed, one of which is the Learning media. Learning Media is constantly evolving with the current era. In determining the Learning media, there are many things to consider, both the state of students, teachers, and the surrounding environment—moreover, the use of learning media develops students ' ability to speak using Arabic. Speaking skills are skills that become a benchmark for someone who is said to be able or proficient in mastering a language. Therefore, the selection of practical and significant media is necessary for the achievement of learning goals that are focused on students ' skills in speaking. In this study, the author uses several media to explore students' speaking abilities. The purpose of this study is to 1) Determine the process of using media learning Maharaj kalam in Class IX Nurul Yaqin Junior High School Jember and 2) determine the effectiveness of the use of media learning in exploring the ability to speak using Arabic in class IX Nurul Yaqin Junior High School Jember. This study is qualitative research with the descriptive method, using three methods of data collection: observation, interview, and documentation. The results of this study are 1) the process of using Learning media in improving the speaking skills of students to-Las IX Nurul Yaqin Junior High School Jember using PowerPoint media with steps, namely presenting material with PowerPoint, presentation of images, asking students to describe or explain the pictures or videos gave, questions and answers and closing learning activities. 2) observations and interviews show that students ' learning spirit increases so they can understand the material and practice it easily. So, it can be concluded that using Learning media effectively improves the speaking skills of Class IX students of Nurul Yaqin Junior High School Jember. انطلاقا من تحقيق الوصول إلى الأهداف التعليمية، لكان التعليم لفي حاجة إلى العناصر العديدة ، منها الوسائل التعليمية. تتطور الوسائل التعليمية دائما مع تدفق العصر. عند تحديد الوسائل التعليمية ، يجب مراعاة العديد من الأشياء ، سواء حالة الطلاب والمعلمين والبيئة المحيطة, لاسيما في استخدام الوسائل التعليمية في تنمية قدرة الطلاب على الكلام باللغة العربية. مهارة الكلام هي مهارة تصبح معيارا لشخص ما ليكون قادرا أو بارعا في إتقان لغة. لذلك ، هناك حاجة ماسة لاختيار الوسائل التعليمية الفعالة والهامة من أجل تحقيق أهداف التعلم التي تركز على مهارات الكلام لدى الطلاب. كان الغرض من هذا البحث هو 1) لاكتشاف عملية استخدام الوسائل التعليمية لتنمية مهارة كلام في لدى طلبة الفصل التاسع في مدرسة نور اليقين الثانوية بجمبر (2) لمعرفة فاعلية استخدام الوسائل التعليمية لتنمية مهارة كلام في لدى الطلبة الفصل التاسع في مدرسة نور اليقين الثانوية بجمبر. هذا البحث هو بحث نوعي بالمنهج الوصفي باستخدام ثلاث طرق لجمع البيانات وهي الملاحظة والمقابلات والتوثيق. نتائج هذه الدراسة هي 1) عملية استخدام الوسائل التعليمية لتنمية مهارة كلام لدى الطلبة الفصل التاسع في مدرسة نور اليقين الثانوية بجمبر باستخدام وسائط باور بوينت مع خطوات ، وهي افتتاح التعليم, وعرض المواد مع نقاط القوة ، وتقديم الصور ، وطلب من الطلاب أن يصفوا أو يشرحوا الصور أو الفيديوهات المعروضة, والأسئلة والأجوبة, واختتام أنشطة التعليم. 2) أظهرت نتائج الملاحظات والمقابلات أن حماس الطلاب للتعلم زاد ، حتى يتمكنوا من فهم المادة وممارستها بسهولة. لذلك يمكن الاستنتاج أن استخدام الوسائل التعليمية فعال لتنمية مهارة كلام في لدى طلبة الفصل التاسع في مدرسة نور اليقين الثانوية بجمبر.